Resistência ao riscamento do aço AISI 420 nitretado a baixa temperatura - Souza, Andrey Serafin de (2022)
At engineering field, the study to improve certain material properties has become more usually, because the industry needs better alternatives with better performance, mainly in wear, corrosion and fatigue, which are the most common reason for engineering artefacts failure. One way to get better performance in properties such as wear and corrosion is the superficial treatment of nitriding, this treatment promotes nitrogen superficial enrichment, producing a layer with high hardness. With that, this paper intends to evaluate if there is an improvement in wear resistance after low temperature plasma nitriding under the martensitic substrate of AISI 420, seeing that it will allow a more structured knowledge of tribological wear mechanisms from a material obtained by a process of superficial enrichment. To do it, nitrided samples were studied and this samples were nitrided at low temperature (380 °C) for 2, 4 and 6 hours, where the low temperature nitriding was made after the heat treatment of quenching and tempering. As reference point from comparison, the AISI 420 quenching and tempering was selected. The analysis shows that the treated samples have a smaller wear area than the reference state, with about 20% of wear area reduction. Furthermore, from plastic deformation of pile ups, there was a reduction of about 70% of deformation presents on wear track with high force charges (20 to 35 N). Therefore, the nitrided samples show better wear resistance when compared to the reference state.